HUBUNGAN POLA ASUH ORANG TUA TERHADAP KEMAMPUAN KOGNITIF ANAK PADA USIA 4-5 TAHUN DI TA AL-IKHLAS MALANG - Iin Fitriani; Mutiara Sari Dewi; Ari Kusuma Sulyandari (Jurnal Dewantara, 2022)
The purpose of this study was to determine the relationship between parenting styles and cognitive abilities of children aged 4-5 years in the application of parents to children to obtain optimal cognitive development. The research subject were 99 fourth year students majoring in early childhood Islamic education at the Islamic University of Malang. The instruments used are questionnaires and documentation. The questionnaire used was the Likert scale of parenting on the cognitive abilities of children aged 4-5 years. Documentation instrument in the form of the value of the results of research on parents. The results showed that the normality test obtained a significant value between the two variables X and Y (0,200 > 0,05 and 0,077 > 0,05), meaning that the value of the two variables were normality distributed. While in hypothesis testing, the value between the two variables X and Y is (0,000 > α = 0,05), then the two variables are stated to have a significant (positive) relationship and Ha is accepted. Then for the t-test results seen from t-count > t-table the value obtained from the two variables X and Y is 8,302 > 2,304, then there is a significant relationship between parenting pattens and cognitive abilities of children aged 4-5 years. With that it can be said from the result obtained that Ha can be accepted and Ho is rejected.